2021
DOI: 10.1093/police/paab001
|View full text |Cite
|
Sign up to set email alerts
|

Mass mobilization for police accountability: The case of Nigeria’s #EndSARS protest

Abstract: Organized public protests against police organization are a rare occurrence in Nigeria. However, between November 2017 and October 2020, a series of online and offline protests organized under the umbrella of #EndSARS campaign was staged against the operation of the Special Anti-Robbery Squad (SARS) unit of the Nigeria Police Force. Thus, this article X-rayed the circumstances that led to the emergence of the #EndSARS protest as a strategic means for seeking police accountability, and the impact of the mass ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 16 publications
1
15
2
1
Order By: Relevance
“…Applying the same argument to the police context, it can be asserted that police performance is a significant determinant of developing and enhancing trust among citizens. In addition, police accountability considers law enforcement and is associated with police responsibility for efficiently providing services of maintaining law and order and controlling crimes by fairly treating individuals under the jurisdiction of the laws (Ojedokun, Ogunleye, & Aderinto, 2021). White et al (2021) reported that police could enhance trust among the citizens by increasing legitimacy, ensuring community ownership, continuously improving their services, and ensuring law and order situations in this country.…”
Section: Literature Review and Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…Applying the same argument to the police context, it can be asserted that police performance is a significant determinant of developing and enhancing trust among citizens. In addition, police accountability considers law enforcement and is associated with police responsibility for efficiently providing services of maintaining law and order and controlling crimes by fairly treating individuals under the jurisdiction of the laws (Ojedokun, Ogunleye, & Aderinto, 2021). White et al (2021) reported that police could enhance trust among the citizens by increasing legitimacy, ensuring community ownership, continuously improving their services, and ensuring law and order situations in this country.…”
Section: Literature Review and Theoretical Frameworkmentioning
confidence: 99%
“…Dong and Kübler (2021) also reported the significance of public institutions' performance in satisfying the public related to various matters. Likewise, police accountability is associated with the communication of the vigilance and transparency of the actions and working patterns to ensure peace and harmony in the country (Ojedokun et al, 2021). This accountability acts as a signal to satisfy the public with police services, resulting in a higher level of trust.…”
Section: Citizen Satisfaction As a Mediatormentioning
confidence: 99%
“…When implemented in the Global South, these models create rifts between security agents and civilians and result in a display of laxity and incompetence, a compromising of ethical standards, and an increase in insecurity. Nevertheless, some countries in the Global South like Nigeria and Cameroon have applied Western models, with negative consequences, including the high record of human rights abuses and brutality by security personnel (Aborisade, 2021;Ojedokun et al, 2021).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Social media, amongst other things, have also given people the opportunity to obtain information from individuals directly rather than relying on existing knowledge from a media organization. As the increase on the web 2.0 technology usage made global waves, the Nigerian community also experienced a massive surge in social media usage, which has benefited the different social movements witnessed in the past two years, including the #EndSARs social training that gained global visibility [11]. Social movements have played an essential role over the decade in Nigeria.…”
Section: Social Media's Impacts On #Endsars# Protestsmentioning
confidence: 99%
“…Social movements historically involve these key actors leading and organizing the protests. However, social media has successfully replaced the pre-existing mobilization structures and has become a critical tool in organizing and coordinating social movements globally [11].…”
Section: Social Media's Impacts On #Endsars# Protestsmentioning
confidence: 99%